BEBERAPA METODE PENGAMBILAN EKTOPARASIT PADA BURUNG MERPATI POS (COLUMBA LIVIA GMELEN) - AZIZ, JANITA; AMIR, M. (BERITA BIOLOGI, 1988)
JANITA AZIZ & M. AMIR. 1988.Some ectoparasites collecting methods of racing pigeon (Columba livia Gmelin). Berita Biologi 3(8):382 - 385.Extraction of ectoparasites of living racing pigeons was done using modified "Fait Isle".The insectisides used for the extraction were pyrethrum,caumaphos and chloroform.The number of acarines extracted during the night was higher than that during the day.In addition insecticides spraying treatment extracted more acarines than fumigation.From the 3 kinds of insecticides used,chloroform proved to kill more acarines than the other two insecticides.